Day 2 Wed, February 10, 2016 2016
DOI: 10.2118/179124-ms
|View full text |Cite
|
Sign up to set email alerts
|

Perforation Cluster Efficiency of Cemented Plug and Perf Limited Entry Completions; Insights from Fiber Optics Diagnostics

Abstract: It is now well established that the production from horizontal wells completed via hydraulic fracture stimulations (fracs) is highly variable along the length of the wellbore. In addition to subsurface conditions, elements of the completion design, such as fluid volume, proppant tonnage, rate, stage length, the number of perforation clusters and their spacing, influence the performance of individual stimulated intervals and wells. Information about completion efficiency can be obtained using Fiber Optic (FO) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(17 citation statements)
references
References 10 publications
(4 reference statements)
0
17
0
Order By: Relevance
“…As previous field observations [16][17][18] and numerical studies [19][20][21] showed, multistage hydraulic fractures might not propagate uniformly, yet planar and biwing fractures are assumed in the model. The hydraulic fractures described in the reservoir model implies hydraulically induced and also propped fractures which indeed contribute fluid production of stimulated wells.…”
Section: 2mentioning
confidence: 95%
See 1 more Smart Citation
“…As previous field observations [16][17][18] and numerical studies [19][20][21] showed, multistage hydraulic fractures might not propagate uniformly, yet planar and biwing fractures are assumed in the model. The hydraulic fractures described in the reservoir model implies hydraulically induced and also propped fractures which indeed contribute fluid production of stimulated wells.…”
Section: 2mentioning
confidence: 95%
“…The presented study only utilizes production history data and reservoir simulation to calibrate the hydraulic fracture parameters. However, integrating recently advanced measurements and techniques such as distributed acoustic sensor (DAS), distributed temperature sensor (DTS) [17,28,29], and seismic wave information [30][31][32] would definitely help better understand geometry and properties of hydraulic fractures.…”
Section: Parametersmentioning
confidence: 99%
“…Finally, Ugueto et al. (2016) conclude that only half or two thirds of the perforation clusters are properly fractured or produced at significant rates after integrating distributed temperature sensing (DTS) and DAS with hydraulic fracture stimulation treatment data for five wells with a total of 120 perforation clusters.…”
Section: Introductionmentioning
confidence: 99%
“…One usually considers that increasing the perforation clusters in one stage can generate a similar number of fractures after hydraulic fracturing. However, production logging and tracer detection demonstrated that not all fractures along the horizontal wellbore can effectively propagate [11][12][13][14][15]. Fracturing fluids and proppants do not enter into each cluster evenly.…”
Section: Introductionmentioning
confidence: 99%